Actinomycosis presenting as an isolated pleural effusion in a patient with an HIV infection: a case report and literature review - Jung Wan Park (BMC, 2021)
Abstract Background Thoracic actinomycosis is an uncommon, chronic, and progressive infection, especially in patients with HIV. We report a case of thoracic actinomycosis presenting as an isolated pleural effusion in a patient with an HIV infection. Case presentation A 68-year-old patient with progressive dyspnea and fever was admitted. On the right side, an ipsilateral massive pleural effusion was confirmed on the chest radiograph, and an HIV infection was newly diagnosed. A pleural biopsy was performed for the further differential diagnosis of potential opportunistic infections and malignancies. The pathology findings were consistent with actinomycosis. Conclusions Active diagnostic approaches such as a pleural biopsy should be considered for indeterminate pleural effusions in immunocompromised patients.